Teaching Sports in Physical Education. Issue 1 (2nd January 2022) - Ward, Phillip; Dervent, Fatih; Iserbyt, Peter; Tsuda, Emi
Abstract : In Physical Education Teacher Education programs, we argue that a focus on fewer models to be taught and learned would provide time for higher competence to be attained by preservice teachers in a curriculum limited in terms of contact hours. During their teacher training, preservice teachers should be given ample opportunities to practice the model and reflect upon their effectiveness in teaching it. We conclude the article by addressing in-service teachers and recommend starting with a model they find appealing in a content domain they are familiar with, and to tinker with their teaching to become more competent.